Psychological intervention in labour market policies - Baiano, Donato (Quaderni di Psicologia Clinica, 2022)
The article proposes the report of an intervention conducted by the author, as collaborator of a technical agency of the Ministry of Labour and Social Policies. The intervention concerned the implementation of a new Italian law which established a jobseekers’ allowance (Reddito di Cittadinanza, law 4/2019), providing career consultancy paths for the applicants. The author proposes specific psychological categories, useful for treating the variability of the demands, in order to develop the client-orientation of Public Services in this field also known as welfare, and usually organized by criteria deriving from other disciplines (such as Law and Economics). The psychological function allows us to propose hypotheses about the relation between the consultancy service and its clients, in order to recognize their motivations, desires and objectives when designing professional development plans; so developing the client-orientation of the service itself.
Keywords: Public Job Centers; jobseekers allowance; income support; career guidance; organizational competence; welfare